Struktur Kepemilikan Dan Faktor – Faktor Yang Mempengaruhi Manajemen Laba Riil - Sepvianti, Meta; Rudyanto, Astrid (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This study aims to provide empirical evidence that ownership structure consisting of managerial ownership and institutional ownership, along with several other factors has an influence towards real earnings management. This research uses data obtained from manufacturing companies that has consistently been listed in Indonesia Stock Exchange for the 2019-2021 period. This study used multiple regression and was processed using the Statistical Package for the Social Sciences (SPSS). The results of this study indicate that the factors that influence real earnings management are audit quality, firm age, and profitability. Meanwhile, ownership structure (managerial ownership and institutional ownership), firm size, and leverage do not influence the company's decision to carry out real earnings management.